Thermoanalytical study of some anti-inflammatory analgesic agents - Bannach, Gilbert [UNESP]; Arcaro, R.; Ferroni, D. C.; Siqueira, A. B.; Treu-Filho, O. [UNESP]; Ionashiro, Massao [UNESP]; Schnitzler, E. (Springer, 2010)
Thermogravimetry (TG), differential thermal analysis (DTA), differential scanning calorimetry (DSC) as well as X-ray diffraction powder (DRX) patterns and Fourier transformed infrared spectroscopy (FTIR) were used to study ketoprofen, ibuprofen, and naproxen. The chemical or physical properties of the studied compounds were established and when possible by X-ray powder diffractometry and/or infrared spectroscopy were used. In this investigation, quantum chemical approach was used to determine the molecular structures using Becke three-parameter hybrid method and the Lee-Yang-Par (LYP) correlation functional. The performed molecular calculations in this work were done using the Gaussian 03 routine. Theoretical calculations help in interpretations of FTIR spectra supplying structural and physicochemical parameters.
Keywords: Ketoprofen; Ibuprofen; Naproxen; Thermal behavior; Infrared spectroscopy; Theoretical calculations